Family caregivers' reported nonadherence to the controller medication of asthma in children in Casablanca (Morocco): Extent and associated factors. (2nd December 2018) - Ménard, Sandra; Jbilou, Jalila; Lauzier, Sophie
ABSTRACT: Objective : Recent statistics show a relatively high prevalence of asthma among Moroccan children and a weak control over their symptoms. To our knowledge, no research has been carried out to document adherence to the controller treatment in this population. This study aims 1) to assess the extent of children's nonadherence to the controller treatment of asthma in an urban region of Morocco as reported by a family caregiver, and 2) to identify the associated factors. Methods : We conducted a cross-sectional study among caregivers of asthmatic children (2–12 years old) in different health and education facilities of Casablanca-Settat. We administered face-to-face questionnaires incorporating validated instruments ( Medication Adherence Rating Scale-Asthma (MARS-A), Beliefs about Medicines Questionnaire (BMQ), Asthma Knowledge Questionnaire). Univariate and multivariate log-binomial regressions evaluating the association between several factors and reported nonadherence were performed (prevalence ratios (PR) and 95% confidence intervals (CI)). Results : Through two public hospitals, three private medical clinics, and one private school, 103 caregivers were recruited. Low adherence to the controller treatment of asthma was reported by 48% of the caregivers (MARS-A <45). In the multivariate model, caregivers with the lowest level of knowledge about asthma were almost three times more likely to report low adherence compared to caregivers with the highest level (PR = 2.93; 95% CI: 1.14–7.52). Conclusions : This study highlights the finding that low adherence is widespread in this context and also the importance of targeting caregivers' knowledge of asthma for interventions.